Institutional transformation through best practices in virtual campus development advancing e-learning policies - Stansfield, Mark, 1963-; Connolly, Thomas (Information Science Reference, 2009)
"This book helps institutions and key stakeholders understand the diverse issues surrounding e-learning and virtual campus initiatives and the conditions necessary to achieve greater success and sustainability"--Provided by publisher.